Posttraumatic stress disorder symptoms and cognitive function in a large cohort of middle‐aged women. Issue 4 (10th January 2017) - Sumner, Jennifer A.; Hagan, Kaitlin; Grodstein, Fran; Roberts, Andrea L.; Harel, Brian; Koenen, Karestan C.
Abstract : Background: Posttraumatic stress disorder (PTSD) has been linked to cognitive decline, but research in women is generally lacking. We examined whether trauma and elevated PTSD symptoms were associated with worse cognitive function in middle‐aged civilian women. A secondary objective was to investigate the possible role of depression in the relation of PTSD symptoms to cognitive function. Methods: The sample comprised 14, 029 middle‐aged women in the Nurses' Health Study II. Lifetime trauma exposure, lifetime PTSD symptoms, and past‐week depressive symptoms were measured in 2008. Cognitive function was measured in 2014–2016 using the Cogstate Brief Battery, a self‐administered online cognitive battery that assesses psychomotor speed, attention, learning, and working memory. We used linear regression models to estimate mean differences in cognition across PTSD symptom levels. Results: Compared to no trauma, elevated PTSD symptoms consistent with probable PTSD (i.e., 4+ symptoms on a screening questionnaire) were associated with worse performance on psychomotor speed/attention ( b = −0.08 standard units, p = .001) and learning/working memory ( b = −0.09, p < .001) composites, after adjusting for sociodemographics. Although attenuated, associations remained significant when adjusted for depressive symptoms and other cognitive risk factors. We found the strongest associations among women with comorbid probable PTSD and depression. Conclusions: PTSD symptoms were negatively related to measures of psychomotor speed/attention and learning/working memory in middle‐aged women. Our study adds to a growing literature that suggests that mental disorders are associated with worse cognitive function over the life course.